Bedside lung ultrasound in the critically ill patient with pulmonary pathology: different diagnoses with comparable chest X-ray opacification - Koeze, Jacqueline (Springer, 2012)
The differential diagnosis and treatment of opacifications on the chest X-ray in critically ill patients may be challenging. This holds in particular the patient that suffers from respiratory failure with hemodynamic instability. Opacification in the chest X-ray could be the result of hematothorax, pleural effusion, atelectasis, or consolidation. Physical examination of such patients may not always indicate what the cause of the opacification is and thus may not always help indicate the correct therapeutic approach. In such cases, bedside ultrasound may be very helpful. We present two cases with similar chest X-ray opacifications but different diagnoses established with the help of a bedside lung ultrasound. There is documented accuracy of ultrasound in differentiating pleural effusions from consolidation. Ultrasound is safe and may be an alternative for computed tomography scan in a hemodynamically or respiratory unstable intensive care patient.